Assessment of core strength and stability control abilities for male gymnasts by using HUBER® 360 - Xue, L. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: During past decades, the skills of gymnasts have become more complex and sophisticated in line with the evolution of Code of Point, gymnastics techniques and equipment. The proportion of gymnasts suffering from injuries is also increasing caused by high-intensity, high-load training. Both core strength and stability control are extremely important abilities to gymnasts, which not only affect the athletes specific techniques performance, but are also important factors in preventing sports injuries. The purpose of this research is to measure the core strength and stability control abilities and identify the potential injury risks of high-level junior male gymnasts with using the Huber®360 platform. METHODS: Sixteen high-level junior male gymnasts from China were involved within this study. The age, height, and weight of the study subjects are expressed in the form of M±D, which are 15.9±1.4 yr,159.3±9.6cm, and 52.1±8.3kg respectively. Inbody 720 was used to measurement the body composition of the subjects. HUBER®360was the instrument used in this research, which is a device with an oscillating platform and two handles, as well as force sensors situated beneath the motorized platform and at the handle level. The Huber 360 software can be used for objectively assessment with a series of seven functional tests. According to the study purpose and objectives, out of the 7 tests, we shall only use two tests, the Stability limit test and Maximum strength test. RESULTS: All the study subjects completed all the tests. 1. Body composition. The average body fat percentage of the 16 gymnasts is 5.4±2.7% (range from 3.0% to 12.0%), which is an excellent data for male gymnast. The low level of body fat percentage is not only the result of long-term training, but also the specific requirement of gymnastics. From the perspective of muscle mass distribution, there is no difference in muscle mass of the group of gymnasts investigated between the left and right upper limbs (3.0±0.7kg,3.0±0.7kg) and lower limbs (7.1±1.3kg,7.1±1.3kg). 2. Stability limit test. Considering the comparison of symmetry in the diagonal direction, the result demonstrated that four subjects showed diagonal advantage characteristic, that is, the data of result are very symmetrical in all four diagonal directions. Seven subjects showed a medium symmetrical in most diagonal directions. Four subjects showed unilateral dominance characteristic, the right side result of three of them is larger than left, and the other one is opposite. Only one subject showed relatively big differences between the front and back side. 3. Maximum strength tests. Considering the unilateral maximum strength difference between the push and pull, and the maximum strength difference of push (or pull) between the left and right side, the result demonstrated that five subject showed perfect balance in the comparation of unilateral or bilateral strength. Seven subjects` results showed that the bilateral strength is balance, CONCLUSION: The study describes a preliminary test conducted on sixteen high-level junior male gymnasts with the HUBER®360platform. The tests and the findings are of great significance, which not only give suggestion that some gymnasts may be at risk for injury due to strength imbalances, and also point out the direction of next-step training.